Asymmetrical linkages between foreign exchange and stock markets: Empirical evidence through linear and non-linear ARDL - Rabia Luqman; Rehana Kouser (Journal of Risk and Financial Management, 2018)
The symmetrical relationship between currency and equity markets has gained much attention among academicians and policy makers in the recent era. Many studies conducted on this relationship have concluded that there is short-run relationship between these variables and found less evidence about a long-run relationship. Moreover, all previous studies supposed the linear or symmetrical relationship between these variables. In this study, we use daily time series data from G8+5 countries and Pakistan for 2000-2016 and apply linear and non-linear autoregressive distributed lag (ARDL) to check the symmetrical and asymmetrical relationship between currency and equity markets. Results have shown that there are asymmetrical linkages between the currency and equity markets.
Keywords: 330; asymmetric linkages; linear and non-linear autoregressive distributed lag (ARDL); currency and equity markets; volatility